2017
DOI: 10.1371/journal.pbio.2002117
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical patterning modes orchestrate hair follicle morphogenesis

Abstract: Two theories address the origin of repeating patterns, such as hair follicles, limb digits, and intestinal villi, during development. The Turing reaction–diffusion system posits that interacting diffusible signals produced by static cells first define a prepattern that then induces cell rearrangements to produce an anatomical structure. The second theory, that of mesenchymal self-organisation, proposes that mobile cells can form periodic patterns of cell aggregates directly, without reference to any prepattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
174
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(181 citation statements)
references
References 85 publications
(140 reference statements)
5
174
2
Order By: Relevance
“…Previous studies have demonstrated that cell aggregation is the cellular mechanism inciting DC formation (Biggs et al, 2018; Glover et al, 2017), but when the DC niche fate is acquired and how this timing relates to placode progenitor specification remains unknown. To identify potential DC-fated precursors before cluster formation and niche establishment, we followed up on our previous work where we isolated with fluorescence-activated cell sorting (FACS) the DC as GFP + cells from embryonic Sox2 GFP knock-in reporter skin (Figure S1A) (Sennett et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that cell aggregation is the cellular mechanism inciting DC formation (Biggs et al, 2018; Glover et al, 2017), but when the DC niche fate is acquired and how this timing relates to placode progenitor specification remains unknown. To identify potential DC-fated precursors before cluster formation and niche establishment, we followed up on our previous work where we isolated with fluorescence-activated cell sorting (FACS) the DC as GFP + cells from embryonic Sox2 GFP knock-in reporter skin (Figure S1A) (Sennett et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have further demonstrated that FGF signaling is required for cell migration to form mature DC clusters, however it is unclear whether it regulates DC fate acquisition itself (Biggs et al, 2018; Glover et al, 2017). Having discovered unclustered DC precursors prior to formation of mature DC, we next asked whether Fgf20 is required for induction of the pre-DC fate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the events that lead to DC cell specification and DC formation remain sparsely delineated. Previous studies, including those using bulk RNA-sequencing and live imaging, have characterized some of the signals and cell behaviors of differentiated DC cells once placodes are histologically apparent (Biggs et al, 2018; Glover et al, 2017; Sennett et al, 2015; Tsai et al, 2014). While these studies uncovered mechanisms by which differentiated DC cells condense into a morphological DC, the events that precede DC cell differentiation are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies uncovered mechanisms by which differentiated DC cells condense into a morphological DC, the events that precede DC cell differentiation are largely unknown. Two studies suggested that DC cells are specified from apparently equivalent upper dermal cells in response to nearby epithelial placode signals (Biggs et al, 2018; Glover et al, 2017). These differentiated DC cells exit the cell cycle, migrate, and undergo cell shape changes to form a dense cluster.…”
Section: Introductionmentioning
confidence: 99%